Beyond bispecificity: Controlled Fab arm exchange for the generation of antibodies with multiple specificities. Issue 1 (31st December 2022) - Yanakieva, Desislava; Pekar, Lukas; Evers, Andreas; Fleischer, Markus; Keller, Stephan; Mueller-Pompalla, Dirk; Toleikis, Lars; Kolmar, Harald; Zielonka, Stefan; Krah, Simon
ABSTRACT: Controlled Fab arm exchange (cFAE) has proven to be a generic and versatile technology for the efficient generation of IgG-like bispecific antibodies (DuoBodies or DBs), with several in clinical development and one product, amivantamab, approved by the Food and Drug Administration. In this study, we expand the cFAE-toolbox by incorporating VHH-modules at the C-termini of DB-IgGs, termed DB-VHHs. This approach enables the combinatorial generation of tri- and tetraspecific molecules with flexible valencies in a straightforward fashion. Using cFAE, a variety of multispecific molecules was produced and assessed for manufacturability and physicochemical characteristics. In addition, we were able to generate DB-VHHs that efficiently triggered natural killer cell mediated lysis of tumor cells, demonstrating the utility of this format for potential therapeutic applications.